PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA PT GLOBAL SERVICE WISATA KOTA JAKARTA SELATAN - Abiyan Ziyaad Sarosa; Ali Mubarok (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstract. The purpose of this study is to determine the effect of service quality and price on purchasing decisions at PT Global Service Wisata, both partially and simultaneously. This research employs an associative quantitative method with data collection conducted through the distribution of questionnaires. The sampling method used is probability sampling with a simple random sampling technique based on the Slovin formula, involving 100 respondents. Data analysis was performed using hypothesis testing with SPSS version 26. The results indicate that service quality and price variables have a significant influence on purchasing decisions at PT Global Service Wisata, both partially and simultaneously. Based on the partial statistical test (t-test), the tvalue for service quality is 8.113 > ttable 1.984, which means Ha1 is accepted and H01 is rejected, indicating a significant effect on purchasing decisions. For the price variable, the tvalue is 1.998 > ttable 1.984, meaning Ha2 is accepted and H02 is rejected. Simultaneously, the Fvalue value is 178.090 > Ftable 3.09 with a significance level of 0.000 < 0.05, indicating that H03 is rejected and Ha3 is accepted. The coefficient of determination result shows that service quality and price contribute 78.6% to purchasing decisions, while the remaining 21.4% is influenced by other variables outside this study. Keywords: Service Quality, Price, Purchasing Decision